Profesionalisme Guru Dalam Pendidikan Berbasis Multikultural Di Sekolah - Nana Mardiana; Atin Supriatin; Musyarapah (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2026)
Instilling multicultural Islamic values ​​through education requires efforts from educational actors. Teachers as educational actors in instilling multicultural Islamic values ​​in schools must have an understanding of multiculturalism. ThroughLibrary Research In this article, it is concluded that Professional teachers are teachers who are able to respect their students and provide opportunities for all students to reach the highest level, regardless of their social status, gender, religion and culture. Managerial basic skills that must be possessed by a teacher in the management of multicultural students related to learning management and classroom management, including Conceptual Skills (Conseptual Skill), Human Skills (Humanity Skill), Technical Skills (Technical Skill), Time Management Skills, and Decision Making Skills.